Diffusion and implementation of innovation in Binuang agricultural training farmer groups - Marhaeni Fajar Kurniawati Kurniawati; Agus Sumantri; Rustono Farady Marta; Engliana Engliana; Helmi Azahari (Jurnal Studi Komunikasi, 2023)
To understand the Diffusion of Innovation and its impact on achieving organisational goals, this research investigates the utilisation of the D-Corp Division Model Based on Corporation, an innovative approach implemented within farmer groups and associations to establish the Division of Agricultural Training in Binuang. Employing a quantitative survey method, the study conducts regression analysis to ascertain the significance of relationships between variables. The findings reveal that the Diffusion of innovation variable demonstrates a significant effect on other variables, as evidenced by the tcount value (1.660) exceeding the critical ttable value (3.197) at a level of significance below the table score (0.002 < 0.05). Consequently, the initial hypothesis (a) is accepted, implying that the Diffusion of Innovation does not significantly influence the application of Innovation. On the other hand, the Innovation Variable exhibits a tcount value (5.003) more significant than the critical ttable value (1.660) with an influence score below the table score (0.000 < 0.05). Thus, the second hypothesis is accepted, indicating a substantial partial influence of Innovation on the application of Innovation in this study. Moreover, the Diffusion of Innovation and work innovation have a combined impact on the research data (0.000 < 0.05, Fcount = 34.663 > Ftable = 3.07). Consequently, Ha3 is accepted, signifying a simultaneous correlation between two independent variables: the innovation diffusion variable (X1) and work innovation variable (X2) concerning the application of innovation (Y) variable.